2013
DOI: 10.3928/01477447-20131021-19
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Instability With and Without Trochlear Dysplasia: New Arthroscopic Medial Soft Tissue Plication With Pullout Technique

Abstract: The aim of this study was to analyze clinical and radiologic results of an arthroscopic medial plication with the pullout technique and to define indications and limitations of this procedure for patellar instability. Records of 45 patients treated for patellar instability with arthroscopic medial plication with the pullout technique were reviewed. The mean patient age was 22.8±8.3 years. The tibial tuberosity-trochlear groove distance, trochlear depth (TD), and Insall-Salvati ratio were measured using magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
(77 reference statements)
2
10
0
Order By: Relevance
“…This is consistent with other literature on the success rate of MPFL-I. 22,23 Interestingly, there were more patients with highgrade dysplasia in the MPFL-R group. This between-groups difference likely represents purposeful selection bias in the à la carte surgical approach, whereby patients with more pathoanatomic risk factors such as trochlear dysplasia are selected to receive a more robust procedure.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with other literature on the success rate of MPFL-I. 22,23 Interestingly, there were more patients with highgrade dysplasia in the MPFL-R group. This between-groups difference likely represents purposeful selection bias in the à la carte surgical approach, whereby patients with more pathoanatomic risk factors such as trochlear dysplasia are selected to receive a more robust procedure.…”
Section: Discussionsupporting
confidence: 93%
“…The main finding in this study was a statistically significant correlation between measures of trochlear dysplasia and QOL physical symptoms scores, an average of 2 years following patellofemoral stabilization surgery. This statistically significant finding aligns with previous research that demonstrated poorer clinical outcomes for MPFL imbrication 22,23 and MPFL reconstruction 18,19,21,31 in patients with high-grade trochlear dysplasia. This study used a disease-specific patient-reported outcome measure as an assessment tool, and therefore provided further evidence that trochlear dysplasia is a predictor of surgical outcome in patients with patellofemoral instability.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, other studies have demonstrated an increased rate of redislocation after MPFL reconstruction or imbrication alone in the setting of trochlear dysplasia. 1,16,24…”
mentioning
confidence: 99%